1998
DOI: 10.1021/jp980717x
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of Coumarin 480 in Vesicles

Abstract: Solvation dynamics of Coumarin 480 (C-480) in dimyristoylphosphatidylcholine (DMPC) vesicles in water is studied using picosecond time-resolved Stokes shift. In sonicated unilamellar DMPC vesicles C-480 exhibits wavelength dependent fluorescence decays. At short wavelengths a fast decay is observed while at the long wavelengths a growth in the nanosecond time scale precedes the decay. The solvation dynamics of C-480 in DMPC vesicles is found to be bimodal with two components of 0.6 and 11 ns, which is similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 38 publications
4
103
0
5
Order By: Relevance
“…3, 13 However, the dynamics in the gel is much faster than the nanosecond dynamics observed in cyclodextrin, 3 microemulsions, 5 micelles, 11 or lipids. 10 The rotational relaxation study also suggests that the probe C-480 remains highly mobile within the sol-gel matrix. It may be recalled that steady state anisotropy in a titania gel indicates that though the bulk viscosity is extremely high, the local microviscosity is extremely low.…”
Section: Discussionmentioning
confidence: 94%
“…3, 13 However, the dynamics in the gel is much faster than the nanosecond dynamics observed in cyclodextrin, 3 microemulsions, 5 micelles, 11 or lipids. 10 The rotational relaxation study also suggests that the probe C-480 remains highly mobile within the sol-gel matrix. It may be recalled that steady state anisotropy in a titania gel indicates that though the bulk viscosity is extremely high, the local microviscosity is extremely low.…”
Section: Discussionmentioning
confidence: 94%
“…14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites. 4 ͑The solvent relaxation dynamics for Coumarin 480 in bulk aqueous solution takes place in 310 fs.…”
Section: Experimental Workmentioning
confidence: 99%
“…One example is the work of Bhattacharyya and co-workers who have measured the time-dependent Stokes shift ͑with ϳ80 ps resolution͒ of the same dye molecule, Coumarin 480, in solventless zeolites, 10 aqueous micelles, 11 and in water pools in a sol-gel matrix 12 and vesicles. 13 Due to their limited time resolution they are only able to probe longer-time solvation dynamics which they found depend strongly on the environment. For example, the long-time decay is ϳ0.8 ns in the sol-gel matrix, 12 0.6 -2.4 ns in micelles ͑using different surfactants͒, 11 11 ns in vesicles, 13 and ϳ15.4 ns in the solventless zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…13 Due to their limited time resolution they are only able to probe longer-time solvation dynamics which they found depend strongly on the environment. For example, the long-time decay is ϳ0.8 ns in the sol-gel matrix, 12 0.6 -2.4 ns in micelles ͑using different surfactants͒, 11 11 ns in vesicles, 13 and ϳ15.4 ns in the solventless zeolites. 10 ͑The solvent relaxation dynamics for Coumarin 480 in bulk aqueous solution takes place in 310 fs.…”
Section: Introductionmentioning
confidence: 99%